Zooplankton Diversty in Ajeet Sagar Dam, Khetri, Jhunjhunu, District, Rajasthan: Exploring Zooplankton Diversity in Ajeet Sagar Dam, Khetri, Jhunjhunu District, Rajasthan (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Zooplankton plays an important role in determination of water quality which occurs in all types of aquatic ecosystems, they play a vital role in energy transfer in an aquatic ecosystem. The aim of present investigation is to know the diversity of Zooplankton groups found in ajeet sagar dam, Khetri, Jhunjhunu District, Rajasthan. In the present study 16 species of zooplankton were identified. The results of present study reveal that Cladocerons and Rotifera dominated in the water station A and B respectively.